Jus Ad Bellum, Values, and the Contemporary Structure of International Law. Issue 1 (27th January 2013) - Murphy, Sean D.
Abstract In "Religion, Violence, and Human Rights: Protection of Human Rights as Justification for the Use of Armed Force, " James Johnson discusses an important dilemma for contemporary society: when should transnational military force be permitted to protect human rights? Professor Johnson uses the relatively recent doctrine of a "responsibility to protect" as the centerpiece of his paper, characterizing it as a reaction to legal concepts that emerged in the "Westphalian system." Yet the doctrine, at least as it relates to the use of military force, is not a reaction to that system but, rather, to the relatively recent system of the UN Charter, particularly its relegation to the Security Council of the exclusive authority to determine when military force should be used for purposes other than self‐defense. When the Cold War ended and the Security Council failed to act to protect human rights, the doctrine was born.